Re-irradiation new frontiers - Nieder, C. (Carsten) 1964-.; Langendijk, Johannes A.; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
New developments such as refined combined modality approaches and significant technical advances in radiation treatment planning and delivery are facilitating the re-irradiation of previously exposed volumes. As a consequence, both palliative and curative approaches can be pursued at various disease sites. Re-irradiation: New Frontiers is the first book to provide a comprehensive overview on current re-irradiation strategies. Re-irradiation methods, technical aspects, the role of combined therapy with anticancer drugs and hyperthermia, and normal tissue tolerance are all discussed in detail. In addition, disease-specific chapters document recent clinical results and future research directions. Professionals involved in radiation treatment planning and multimodal oncology treatment will find this book to be an invaluable aid in understanding the benefits and limitations of re-irradiation and in designing prospective trials.
Normal Tissue Tolerance to Reirradiation -- Fractionation Concepts -- Hyperthermia and Reirradiation -- Therapeutic Ratio of Reirradiation with Cytotoxic Drugs and Other Response-Modifying Agents -- Reduced Normal Tissue Doses Through Advanced Technology -- Brain Tumors -- Eye Tumors -- Head and Neck Cancer -- Lung Cancer -- Breast Cancer -- Prostate Cancer -- Rectal Cancer -- Gynaecological Malignancies -- Soft Tissue Sarcomas -- Bone Metastases -- Brain Metastases.
Electronic reproduction.
Keywords: Oncology; Interventional radiology; Electronic books